Implementation of the Best Teacher Performance Evaluation Decision Support System to Optimize Teacher Quality Using TOPSIS and SAW Methods Based on a Website (Case Study: SMP Putra Bangsa, Depok City) - Rio Mukti Setyawan; Sri Rama Putri (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2026)
The process of selecting the best teachers at SMP Putra Bangsa in Depok is currently still conventional and subjective, which poses a risk of assessment errors and a lack of transparency. This study aims to develop a web-based Decision Support System (DSS) capable of optimizing efficiency and objectivity in identifying high-performing teachers. The scope of the study focuses on processing teacher performance data using five main criteria: administration, work discipline, attendance, collaboration, and professional development. The methods implemented were the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) and Simple Additive Weighting (SAW). The results of the study indicate that the developed system successfully integrates both algorithms to generate an automatic and accurate ranking of teachers. The implementation of this system facilitates data processing for schools and enables the presentation of transparent evaluation reports. The main conclusion of this study is that the use of the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) and Simple Additive Weighting (SAW) methods in a web-based system is effective in supporting more objective decision-making, while minimizing subjectivity in the process of evaluating teacher performance in a school setting.